Locked Closets and Fish Bowls: Self-Disclosing Disabilities - Cheuk, Fiona (Critical Disability Discourses, 2012)
The dominant assumption about self-disclosure asserts that sharing information about oneself is solely a matter of individual choice. However in the context of identity disclosures, the aspect of self that is being disclosed is attached to the backdrop of the socio-political environment of which the act and agent are situated in. In this regard, it becomes questionable whether people disclosing socially stigmatized and devalued identities such as disability are truly matters of individual freedoms around choice making. This paper aims to highlight how opportunities for discussing experiences and issues involving one’s disability identity are limited to formalized institutional spaces or silenced in informal spaces due to the authority of medical cognition around disability within western societies. This lessens the control and authority of disabled people over the way in which disability is understood within the society as a homogenized identity defined through third-party authorities and cannot reflect the complex and nuanced identities formed through lived experiences. By examining the parameters of self-disclosure surrounding opportunities to claim and discuss one’s identity with the inclusion of disability(ies), discourses of self-disclosure can be pushed towards informal interpersonal spaces rather than limited formal spaces so as to weaken the attitudinal barriers which form the basis for disabling social structures and creates unequal citizenship. Keywords: self-disclosure, disability, identity-politics, freedom of choice, citizenship.